Market Extreme Moves and the Industries' Probability of Crash and Jump - Bouaddi, Mohammed (Archives of Business Research, 2024)
We investigate the dependence of stock returns in the extreme. We use a flexible model for the probability of extreme moves. The results show that the dependence of industries' returns to the market returns is asymmetric and significant in the extreme. In addition, it shows that; the probability of an industry to crash is at least seven times higher than the probability to jump. The results also highlight that the probability of an industry the crash or jump is higher in non-recession periods than in recession periods due to surprise effect.